Influence of Academic Pressure and Sleep Patterns on Undergraduate Psychological Wellbeing - Stephen Ishola Babatunde; Alliu Sadiat Iyabode; Adebimpe Oluwafisayo Adenike; Oghenetega Elizabeth Wadi; Elizabeth Adeyinka Adebajo (Jurnal Psikologi Teori dan Terapan, 2025)
Background: Increasing academic pressure along with poor sleep hygiene has become a primary concern for students’ mental health in recent years. Objective: This study investigated the independent and combined influence of academic pressure and sleep patterns on psychological wellbeing among undergraduate. Method: This study employed Quantitative using linear regression analysis. The sample consisted of 200 undergraduate selected using stratified random sampling Results: Hypotheses revealed that academic pressure significantly predicted psychological wellbeing (β = .468, p < .001, R2 = 0.219), Sleep patterns also significantly predicted psychological wellbeing (β = –.399, p < .001, R2 = 0.159) and the combined, academic stress and sleep patterns jointly influence psychological wellbeing (R² = .305, F(2,197) = 15.446, p < .001). Conclusion: The study concluded that academic pressure, poor sleep patterns negatively influence the psychological wellbeing of undergraduates. Abstrak Latar Belakang: Tekanan akademik yang meningkat dan pola tidur yang buruk menjadi masalah utama yang memengaruhi kesehatan mental mahasiswa. Tujuan: Penelitian ini bertujuan untuk meneliti pengaruh tekanan akademik dan pola tidur, baik secara terpisah maupun bersama-sama, terhadap kesejahteraan psikologis mahasiswa Universitas Olabisi Onabanjo, serta memberikan wawasan untuk pengembangan program kesejahteraan dan dukungan kesehatan mental. Metode: Penelitian ini menggunakan desain kuantitatif deskriptif korelasional dengan 200 mahasiswa yang dipilih melalui teknik stratified random sampling. Data dikumpulkan menggunakan Academic Stress Scale, Sleep Pattern Questionnaire, dan Ryff’s Psychological Well-Being Scale (α = 0,83–0,85), kemudian dianalisis menggunakan SPSS (Versi 25) dengan analisis regresi. Hasil: Tekanan akademik berpengaruh signifikan terhadap kesejahteraan psikologis (β = 0,468, p < 0,001, R² = 0,219); pola tidur juga berpengaruh signifikan (β = –0,399, p < 0,001, R² = 0,159). Secara bersama-sama, kedua variabel menjelaskan 30,5% variasi kesejahteraan psikologis (F(2,197) = 15,446, p < 0,001). Kesimpulan: Tekanan akademik dan pola tidur yang buruk berpengaruh negatif terhadap kesejahteraan psikologis mahasiswa.